Measurement the levels of toxic metals by using cold vapor atomic absorption spectroscopy technique and measurement of Vit A by using HPLC in autistic children - Abd, Mena Y.; Ibrahim, Israa H.; Hussein, Muna A. (Technium BioChemMed, 2024)
Autism is a neurodevelopmental disorder characterized by stereotypic/repetitive behavior, impaired communication, imagination, and social interactions. Recently, studies have investigated the possible association between the etiology of autism and the potential roles of various environmental agents, especially heavy metals. The present study aimed to examine levels of toxic metals in serum samples of autism. The levels of arsenic, cadmium and lead in serum of this child were determined by atomic absorption spectrometry and compared with those of healthy children who had been assessed in previous studies. The autism had higher levels of Arsenic (65.32 ±7.89) cadmium (10.36±1.06 μg/g) and lead (7.6±0.86 μg/g), as well as significant decrease in the concentration of vitamin A (4.29± 0.66) as comparison with control group.